The Political Origins of Racial Inequality. (September 2017) - Maltby, Elizabeth
Policy feedback theory argues that public policies shape mass political behavior by teaching citizens about their relationship to government. I reevaluate this argument by examining how criminal justice policy shapes the political orientations and participation of blacks and whites. I argue that, because these policies send different messages to blacks than to whites about the treatment they can expect from government, these groups have opposite reactions to criminal justice enforcement. Using data from a 2014 national survey and information on local criminal justice outcomes, I find that racially skewed criminal justice enforcement is associated with negative political orientations and lower rates of political participation for highly educated blacks. I also find that whites respond positively to similar criminal justice outcomes when they reside in areas with large black populations. The results show that unequal policy outcomes lead to political inequality.